New Pseudocercospora species causing foliar diseases in plain forests of Vindhya region in India - KIRTI BHALLA, SANJAY K. SINGH and (Indian Phytopathology, 2002)
This paper deals with descriptions and illustrations of four new species of Pseudocercospora, P. cassiae-sophorae, P. cocculicola, P. eucalypticola and P. kolanensis, occurring on Cassia sophora [C. sophera], Cocculus hirsutus, Eucalyptus sp. and Woodfordia sp., respectively. The fungi were collected from forests of Vindhyan region, Uttar Pradesh.